A Proposed Approach for Web Server Placement Implementation in ARM: Array - Aberomand, Nima (Acta Universitatis Danubius. Communicatio, 2020)
This article developed and implemented an embedded Web server on the S3C44B0X based board by using μClinux operating system as development platform. Two schemes are put forward in this paper: One is an embedded Web server based on boa, the other is an embedded Web server based on HTTP and socket programming. In the first scheme, the main work is to transplant boa in μClinux and to design CGI. The results is realization of dynamic pages and simple control functions. In the second scheme, it is possible to fulfill the GET and POST requests in HTTP and to produce simple dynamic pages.It is also possible to realize the query of history data and some control functions in the request of browser. In this paper, the architecture of embedded Web server and the S3C44B0X development platform is first discussed, the principle and realization of boot loader is also introduced. After that the characteristic of μClinux and network driver is described, including the transplant of μClinux. Then, the principle and mechanism of TCP/IP and HTTP is first discussed and the principle of CGI is also introduced. After that the transplant of boa and the design of CGI and the test of Web server is discussed.